Magnetoresistance of a Polycrystalline InSb Disk with an Embedded Au Core - Suh, Jooyoung; Kim, Wonyoung; Chang, Joonyeon; Han, Suk-Hee; Kim, Eun Kyu (KOREAN PHYSICAL SOC, 2009)
We have investigated the magnetoresistance (MR) of a polycrystalline indium-antimonide (InSb) van der Pauw (vdP) disk with an embedded concentric gold (Au) core. A polycrystalline InSb sample was prepared in a thermal evaporator. The size of the Au core embedded in a InSb disk with a constant 100-mu m diameter varied from 0 to 70 mu m. The MR of the devices with different Au size was measured in order to find the optimum An size and the origin of the enhanced MR. The room temperature MR of the InSb vdP disk with a 70-mu m An inhomogeniety was 614% at 1 T, and 9,900% at 5 T. The MR significantly depended on the size of embedded Au. The results can be well understood by considering field dependent current deflection around the embedded Au core, which is called geometrical MR.
Keywords: INHOMOGENEOUS SEMICONDUCTORS